2022
DOI: 10.3389/fimmu.2022.915246
|View full text |Cite
|
Sign up to set email alerts
|

IL22RA1/JAK/STAT Signaling Acts As a Cancer Target Through Pan-Cancer Analysis

Abstract: Cytokines and cytokine receptors are important mediators in immunity and cancer development. Interleukin 22 (IL22) is one of the most important cytokines which has protumor effect. Given that common and specific roles of cytokines/receptors in multiple cancers, we conducted a pan-cancer study to investigate the role of IL22RA1 in cancer using The Cancer Genome Atlas (TCGA) database. Notably, we found IL22RA1 transcript was upregulated in 11 cancer types compared with their corresponding control. The mRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The increased expression of IL10RB was found to be associated with a poorer overall survival rate in UCEC. This could be attributed to the activation of the JAK/STAT pathway, which facilitates tumor progression [55]. The mRNA expression of CXCL12 was significantly lower in UCEC samples [56].…”
Section: Mlh1 Expression Negatively Correlated With the Tumor Immune ...mentioning
confidence: 99%
“…The increased expression of IL10RB was found to be associated with a poorer overall survival rate in UCEC. This could be attributed to the activation of the JAK/STAT pathway, which facilitates tumor progression [55]. The mRNA expression of CXCL12 was significantly lower in UCEC samples [56].…”
Section: Mlh1 Expression Negatively Correlated With the Tumor Immune ...mentioning
confidence: 99%
“…The JAK/STAT signaling pathway, a critical mediator in various cellular functions, has emerged as a significant player in the progression of cancer, including UM, where its aberrant activation has been linked to increased growth, survival, and malignancy of tumor cells [ 9 , 10 ]. In UM GEPs, the HTR2B (5-hydroxytryptamine receptor 2B) stands out as the most dysregulated mRNA transcript in high-risk MUMs and has connections with the JAK/STAT pathway.…”
Section: Altered Molecular Mechanisms In Ummentioning
confidence: 99%
“…These molecular discoveries have led to the subclassification of UMs which, in turn, has significant prognostic implications and has become integral to patient management, guiding therapeutic decisions and enabling personalized treatment approaches (reviewed in [ 8 ]). Signaling pathways play a pivotal role in tumorigenesis and progression in many cancers, such as the JAK/STAT, mTOR and β-catenin pathways, among others (reviewed in [ 9 , 10 , 11 , 12 , 13 ]). Understanding these pathways and the broader immune microenvironment offers new targets for therapeutic interventions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al identified 11 types of cancer associated with upregulated transcript levels of IL22RA1. 84 The authors noted that patients' poor survival was linked to greater gene expression. IL22RA1 polymorphisms were also linked with chronic rhinosinusitis occurrence and severity.…”
Section: Il-22rα1mentioning
confidence: 99%